PENGARUH EKUITAS MEREK DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PENGGUNAAN JASA EKSPEDISI (STUDI PADA KONSUMEN JALUR NUGRAHA EKAKURIR) - Kirana, Erghana Kanza (Manajemen Bisnis, 2018)
This study aims to examine the impact of brand equity and consumer trust on decision to use the expedition service. The population of this study was the entire customers who sent their package in the JNE Malang; Meanwhile, the sample was 120 consumers who accidentally met while sending their package in the JNE office. The sample was selected by using accidental sampling technique. The data were analysed by means of Multiple Linear Regression. The findings indicated that (1) most of the consumers initially used JNE for the first time in 2014; (2) brand equity significantly influences decision to use the expedition service with the t-count value of 2.350 and the significance value of 0.020; (3) consumer trust also significantly influences decision to use the expedition service with the t-count value of 3.478 and the significance value of 0.001; and last, (4) from these two variables, consumer trust dominantly influences the decision to use the expedition service with a value of 0.301.